Orlicz-Pettis Type Theorems via Strong p-Cesàro Convergence. (19th May 2019) - León-Saavedra, Fernando; Moreno-Pulido, Soledad; Sala, Antonio
Abstract: We obtain a new version of the Orlicz-Pettis theorem within the frame of the strong p -Cesàro convergence.